EFFECT OF SUPPLEMENTATION OF ORGANIC ACIDS ON PRODUCTIVE PARAMETERS OF GUINEA PIGS (Cavia porcellus) - Sánchez-Silva G., Milena (2014)
The objective of the study was to evaluate the effect of the supplementation of organic acids (AO) on the productive parameters of guinea pigs (Cavia porcellus). Eighty male guinea pigs were randomly distributed in 20 experimental units, and these randomly assigned to five treatments: T1: Control (basal diet), T2: Growth Promoter Antibiotic (APC) (basal diet plus 200 ppm Zinc-Bacitracine), T3, T4, and T5: Organic acids (AO) (basal diet plus 100, 200 or 300 ppm respectively, of a mixture of acetic, lactic, and propionic acid in equal proportions). The basal diet was composed of wheat bran and fodder (rye grass plus clover). The animals were exposed to the treatments over 10 weeks. Body weight gain, dry matter intake, and feed conversion ratio (ICA) were evaluated. Significant quadratic response patterns to the AO were observed in body weight gain and ICA (p<0.035 and p<0.005 respectively) where the maximum body weight gain and the best ICA were associated with 173 and 152 ppm of AO respectively. No treatment effects were detected on dry matter intake. It is concluded that the supplementation with OA improved body weight gain and ICA of growing and fattening guinea pigs